Indonesia's Doctors, Midwives and Nurses : Current Stock, Increasing Needs, Future Challenges and Options - World Bank (World Bank, 2012)
This paper is one of several inputs prepared for a comprehensive Health Sector Review that the Government of Indonesia is currently conducting. It compiles, analyzes and interprets available information on Indonesia's health service providers; doctors, midwives and nurses. Within the limitations imposed by questions about the accuracy and timeliness of current workforce data, the paper describes the stock and distribution of health workers. The paper draws attention to weaknesses in the workforce planning methods in use, and then reviews the human resource policies, including governance structures and the regulatory framework, that affect health workers. It concludes by describing future challenges and some suggested ways of addressing these challenges. In brief, this paper identifies a number of main challenges in the health workforce in Indonesia. These are: (i) there is a shortage and inequitable distribution of medical doctors and specialists; (ii) the education of health professionals is of poor quality and the accreditation and certification system is weak; (iii) health workforce policy development and planning are not based on evidence or demand, but rather on standard norms that do not reflect real need or take into account the contribution of the private health sector; nor have they adapted to a decentralized paradigm, and finally; (iv) the growing and changing demand for health care due to demographic and epidemiological changes will increase the burden on the already ineffective health system. The final section of this paper makes nine suggestions designed to address these main challenges.